Pregnancy confirmed COVID-19 in hospital Dr. M. Djamil Padang periode 2020-2021 - Aladin Aladin; Linosefa Linosefa; Muhammad Rafky Alfi Putra (Universitas Andalas, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) caused a highly acute respiratory infection and high mortality. Symptoms of COVID-19 would be more severe if it affects people at high risk, one of which is pregnant women. This study aims to determine the characteristics of pregnant women with confirmed COVID-19 at RUSP Dr. M. Djamil Padang Objective: to find out the profile of the maternal charactheristic confirmed COVID-19 in hospital Dr. M. Djamil Padang Periode 2020-2021. Methods: This type of research is descriptive with a total sampling technique using secondary data, namely patient medical records. The sample of this study were all pregnant women who were confirmed to have COVID-19 at RSUP Dr. M. Djamil Padang for the 2020-2021 period with a total sample of 186 patient medical records. Univariate data analysis is presented in the form of frequency distribution and data processing using the Computerized SPSS version of the IBM version 26.0. Results: The highest age group was 20-35 years old (78%), the most addresses were Padang City (43,5). %), the most gravida status was multigravida (71,5%), the most parity status was multipara (38,2%), the most gestational age was third trimester (81,7%), the most clinical symptoms are asymptomatic (44,1 %), and the most comorbid status was without comorbid (82,3%). Conclusion: The most pregnant women have confirmed COVID-19 at RSUP Dr. M. Djamil Padang in 2020-2021 with characteristics of age 20-35 years, address in Padang City, status of multigravida and multiparous pregnancy, third trimester gestational age, asymptomatic and no comorbidities.